Systematic Literature Review: Development of Comic and E-Comic Media to Improve Students' Numeracy Literacy Ability - Nafila, Valda; Waluya, Stevanus Budi; Sugiman, Sugiman (Polinomial : Jurnal Pendidikan Matematika, 2025)
Developments in the 21st century require adaptation in various aspects of life, including education. However, there are challenges in improving the quality of education as stated in SDGs point 4. One of the success indicators of SDGs point 4 is numeracy literacy. Numeracy literacy is the skill in using various numbers and symbols related to basic mathematics to solve practical problems in a particular context. Media that can improve numeracy literacy skills are comics and e-comics. The purpose of this study is to describe how the application of comics and e-comics to improve numeracy literacy based on publication year, education level, and how the effect of comics and e-comics in improving numeracy literacy. The research method used is Systematic Literature Review (SLR) with the following stages: 1) development of research questions, 2) determination of selection criteria, 3) development of search strategy, 4) study selection process, 5) appraising the quality of studies, and 6) synthesis of results. The data collection technique was carried out by reviewing articles related to the comics or e-comics to improve numeracy literacy skills in articles published in 2021-2025. Through Google Scholar and Scopus, 16 articles were found. The results of this study show that comics and e-comics can improve literacy and numeracy skills.